Esaform 2021 2021
DOI: 10.25518/esaform21.3627
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of effect of printing direction and surface roughness on the mechanical properties of AlSi10Mg-alloy produced by selective laser melting

Abstract: The additive manufacturing has initially gained popularity for production of non-loadbearing parts and components or in the fields where the material strength and ductility are less important such as modelling and rapid prototyping. But as the technology develops, availability of metal additive manufacturing naturally dictates the desire to use the produced components in load-bearing parts. This requires not-only a thorough documentation on the mechanical properties but also additional and independent research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The comparison of different sample sizes and geometries also seems not to have received enough attention in the literature yet. In our earlier work we reported a comparison of strength of SLM-produced AlSi10Mg samples of different diameters [5]. Similar, but more focused study was reported by [6] who compared the strength, the microstructure and the porosity of AlSi10Mg samples of different diameters and reported up to 30% decrease in strength for small struts.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…The comparison of different sample sizes and geometries also seems not to have received enough attention in the literature yet. In our earlier work we reported a comparison of strength of SLM-produced AlSi10Mg samples of different diameters [5]. Similar, but more focused study was reported by [6] who compared the strength, the microstructure and the porosity of AlSi10Mg samples of different diameters and reported up to 30% decrease in strength for small struts.…”
Section: Introductionsupporting
confidence: 69%
“…[8]-[29] Rectangular cross-section samples machined on all sides [3], [30]- [35] Flat cross-section samples cut out of a plate or thin-walled profile [36]- [39] Net shape rectangular cross-section samples that were sandblasted [40] Net shape cylindrical [6], [41]- [43] Mass-produced net shape rectangular samples [44] Understanding the influence of the sample cross-section size on the measured strength is crucial to be able to compare the values of strength reported using different sample geometries. In this article we complement our previous results from [5] with additional study of material microstructure and make a comparison with the results of [6] in order to gain a deeper understanding on how the measured strength and microstructure of SLM-produced AlSi10Mg are affected by the size of printed cross-section.…”
Section: Machined Cylindrical Samplesmentioning
confidence: 93%
See 2 more Smart Citations
“…Most of the research concerns the analysis of the influence of print direction on the dimensional and shape accuracy and the quality of the surface layer of the parts produced, taking into account only the change of print direction [15][16][17]. In most studies, the surface texture is examined by analyzing the 2D or 3D roughness parameters or by applying the multiscale method [18,19].…”
Section: Introductionmentioning
confidence: 99%